Use of flashcard media in improving literacy in writing procedure texts in class VII students of Al-Mauludi Middle School - D. Nurfajrin Ningsih; Eliani Setiadi Putri (Nashir Al-Kutub Indonesia, 2025)
This research aims to explore the application of flashcard media and evaluate its impact on improving students' writing literacy. Using a Pre-experimental Design with a One Group Pretest-Posttest type, the study found that flashcard media positively influenced student behavior in learning to write procedural texts. Observations during the learning process, including the preliminary, core, and closing activities, indicated a high level of engagement, with a final score of 95%, categorized as very good. Statistical analysis revealed a significant increase in student performance, with the average pretest score rising from 58.95 (ranging from 43.75 to 75.00) to an average posttest score of 86.08 (ranging from 62.50 to 93.75), reflecting a difference of 27.13. Therefore, the use of flashcard media is shown to be effective in enhancing writing literacy in procedural texts among seventh-grade students at Al-Mauludi Middle School. The sample in this study consisted of seventh-grade students from Al-Mauludi Middle School, focusing on improving their procedural writing skills through the use of flashcard media. It is recommended that flashcard media be utilized more broadly in educational settings to further support and improve students' writing skills.